A new species of the genus Larutia (Squamata: Scincidae) from Gunung Penrissen, Sarawak, Borneo - Fukuyama, Ibuki; Hikida, Tsutomu; Hossman, Mohamad Yazid; Nishikawa, Kanto (Zootaxa, 2019)
We collected a specimen of a scincid lizard of Larutia Böhme, 1981 from the edge of a primary forest on Gunung Penrissen, Kuching Division, Sarawak, Malaysian Borneo. The single specimen of the new species differs from all other known congeners by the molecular divergence in the mitochondrial ND1 gene and morphological characters including small adult body size (SVL 84 mm); 22 longitudinal scale rows around midbody; first pair of chinshields contacting second infralabial; second pair of chinshields separated from infralabials by an elongated scale; two subdigital lamellae on second toe; and body without yellow or pale bands or spots. It is the ninth species described in the genus and the second species of Larutia in Borneo.